Enterprise, Not Aid, for Social Change - Tan, Kim (Institutional Knowledge at Singapore Management University, 2012)
A wind of change is blowing through the world of aid and philanthropy. The old formula of aid and compassion doesn’t work anymore. In its place, Kim Tanproposes a new model based on enterprise and financial capital.